Pendidikan dalam Konsep Al-Tsabit wa al-Mutahawwil: Kritik Adonis terhadap Stagnasi Kebudayaan Arab-Islam - Lutfiyah Alindah; Muhammad Rokib; Hidayatun Ulfa (Scidac Plus, 2024)
This article seeks to provide a theoretical concept of how to understand Adonis thought. Historical analysis, combine with literary overview, is deployed to trace the empirical passage of Adonis thought on al-Tsabit wa al-Mutahawwil concept. This article argues that al-Tsabit wa al-Mutahawwil is the new concept for Arabs cultural studies. Following this process, the concept of al-Tsabit wa al-Mutahawwil have been found the two mindstream in the Arab world, aql (rational) and naql (texts).